Academic performance, self-reported motivation, and affect in higher education: the role of basic psychological need satisfaction - Mauricio González-Arias; Paula Dibona; Benjamín Soto-Flores; Andrés Rojas-Puelles; Massimo Amato; Diego Álvarez-Trigo; Rodrigo Castillo (Frontiers in Psychology)
IntroductionHigher education is a milestone in students’ lives; however, it often comes with various challenges. In this context, Basic Psychological Needs Theory emerges as a framework to understand a series of significant factors that influence students’ academic experiences, such as motivation and affect. Although there are studies that assess the association between basic psychological needs (BPN), motivation, affect and academic performance separately, there is a lack of research integrating all these variables in a higher education context. The first objective of the study was to evaluate the differences in BPN satisfaction, positive and negative affect, and academic performance between the courses perceived as the most motivating and those perceived as the least motivating. The second objective of the study was to examine the relationship between the studied variables.MethodsThis non-experimental cross-sectional study included a sample of 148 higher education students from Chile. Paired sample t-tests were performed to compare the levels of the study variables between the courses, followed by structural equation modeling (SEM).ResultsFindings for the t-tests reveal that courses considered the most motivating showed higher positive affect, lower negative affect, higher BPN satisfaction, and better academic performance. Results obtained through the SEM show that BPN satisfaction has an indirect effect on academic performance, mediated by affect and self-reported motivation. In addition, a direct effect from negative affect to academic performance was found.DiscussionThese results contribute to a better understanding of how BPN satisfaction influences the academic performance of university students, and reinforce the usefulness of Self-determination Theory (SDT) in explaining motivational and affective phenomena in higher education.